Summary of Audit Judgment from Auditor Experience, Task Complexity, Professional Skepticism, and Goal Orientation - Abimanyu, Putri Regina; Martini, Rita; Indriasari, Desi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The goal of this study was to gather empirical evidence about the effects of auditor experience, task complexity, professional scepticism, and goal orientation on audit judgement. This study's population and sample included 35 respondents, all of whom worked as auditors for the South Sumatra Inspectorate. Questionnaires on a Likert scale of 1 to 5 were distributed directly to auditors to collect data. The data is analysed using Structural Equation Modelling using Partial Least Squares (PLS) and SmartPLS 4.0. The findings of this study revealed that auditor experience and professional scepticism have a favourable and significant effect on audit judgement. Meanwhile, task complexity and goal orientation have a positive but not statistically significant effect on audit judgement. Additionally, auditor experience, task complexity, professional scepticism and goal orientation influence audit judgement at the Inspectorate of South Sumatra Province by 50.6%.